2020
DOI: 10.1055/a-1236-3855
|View full text |Cite
|
Sign up to set email alerts
|

Biceps Tendon Changes and Pitching Mechanics in Youth Softball Pitchers

Abstract: With the lack of pitch count regulation, youth softball pitchers are experiencing unremitting high stresses on the anterior shoulder. The purpose of this study was to examine the association of acute changes in the long head of the biceps tendon with pitching kinematics and kinetics in youth softball pitchers following an acute bout of pitching. Twenty-three softball pitchers (12.17±1.50 yrs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…While previous research has noted that the biceps tendon endures great stress during the windmill pitch, 4,23,33 increased throwing shoulder distraction force linked with increased elbow extension moment might further point to the biceps tendon as a location of injury and anterior shoulder pain among softball pitchers. The biarticular and mechanical nature of the biceps tendon and its influence at the shoulder and elbow joint can make it particularly susceptible to injury.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…While previous research has noted that the biceps tendon endures great stress during the windmill pitch, 4,23,33 increased throwing shoulder distraction force linked with increased elbow extension moment might further point to the biceps tendon as a location of injury and anterior shoulder pain among softball pitchers. The biarticular and mechanical nature of the biceps tendon and its influence at the shoulder and elbow joint can make it particularly susceptible to injury.…”
Section: Discussionmentioning
confidence: 86%
“…In light of the sequential nature of the arm during the pitching motion, more research is needed to understand how these interactions might influence forces at the shoulder joint and potentially help to minimize risk of injury at the shoulder joint. While previous research has noted that the biceps tendon endures great stress during the windmill pitch, 4,23,33 increased throwing shoulder distraction force linked with increased elbow extension moment might further point to the biceps tendon as a location of injury and anterior shoulder pain among softball pitchers. The biarticular and mechanical nature of the biceps tendon and its influence at the shoulder and elbow joint can make it particularly susceptible to injury.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Therefore, excessive IR deficit may aggravate internal impingement, consequently increasing mechanical load and the risk of throwing-related rotator cuff injuries. In human studies, increased mechanical load acutely induced an increase in tendon thickness 43 44 45 46 . Therefore, our result suggested that excessive posterior capsule tightness increased mechanical load with internal impingement, and accumulation of this increased load induced SST abnormalities.…”
Section: Discussionmentioning
confidence: 99%